Arboviruses and the eye. Issue 1 (December 2017) - Andrade, Gabriel; Ventura, Camila; Mello Filho, Paulo; Maia, Maurício; Vianello, Silvana; Rodrigues, Eduardo
Abstract Arthropod-borne viruses, or arboviruses, are viruses that are transmitted through the bites of mosquitoes and ticks. There are numerous arboviruses throughout the world capable of causing human disease spanning different viral families and genera. Recently, dengue, chikungunya, and zika viruses have emerged as increasingly important arboviruses that can cause human disease, however no specific treatment or vaccine is available for them. In addition, ocular manifestations of these diseases have become more prevalent over the past few years. This review highlights the current understanding on the pathogenesis, systemic changes and ocular findings, emphasizing the retinal manifestations related to dengue, chikungunya, and zika viruses.